Comparing Health Care Financial Burden With an Alternative Measure of Unaffordability - Edward S. Kielb BS; Corwin N. Rhyan MPP; James A. Lee MS (SAGE Publishing, 2017)
Health insurance plans with high deductibles increase exposure to health care costs, raising concerns about how the growth in these plans may be impacting both the financial burden of health care expenditures on families and their access to health care. We find that foregoing medical care is common among low-income, privately insured families, occurring at a greater rate than those with higher incomes or Medicare coverage. To better understand the relationship between out-of-pocket (OOP) spending and access, we used the 2011-2014 Medical Expenditure Panel Survey (MEPS) data and a logistic model to analyze the likelihood of avoiding or delaying needed medical care based on health insurance design and other individual and family characteristics. We find that avoiding or delaying medical care is strongly correlated with coverage under a high-deductible health plan, and with depression, poor perceived health, or poverty. However, it is relatively independent of the percent of income spent on OOP costs, making the percent of income spent on OOP costs by itself a poor measure of health care unaffordability. Individuals who spend a small percentage of their income on health care costs may still be extremely burdened by their health plan when financial concerns prevent access to health care. This work emphasizes the importance of insurance design as a predictor of access and the need to expand the definition of financial barriers to care beyond expenditures, particularly for the low-income, privately insured population.